2017
DOI: 10.4166/kjg.2017.70.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Body Mass Index and Chronic Atrophic Gastritis and Intestinal Metaplasia

Abstract: Background/Aims: Chronic atrophic gastritis (AG) and intestinal metaplasia (IM) of the stomach are premalignant lesions. The present study aimed to examine the associations between obesity and these lesions. Methods: A total of 2,997 patients, who underwent gastroscopy, participated in this study, excluding those who had been diagnosed with gastric cancer. Participants were divided into four groups based on their body mass index (BMI). The risk of AG and IM with increasing BMI was analyzed in men and women, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Another cross-sectional study of 617 Japanese individuals showed lower BMI in the atrophic gastritispositive group ascertained by the PG I and PG I/II ratio than in the atrophic gastritis-negative group (23). A cross-sectional study of 217 patients demonstrated an inverse association between BMI and biopsy-proven intestinal metaplasia (24 (25). In the same study, there was no significant association between BMI and atrophic gastritis (25).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Another cross-sectional study of 617 Japanese individuals showed lower BMI in the atrophic gastritispositive group ascertained by the PG I and PG I/II ratio than in the atrophic gastritis-negative group (23). A cross-sectional study of 217 patients demonstrated an inverse association between BMI and biopsy-proven intestinal metaplasia (24 (25). In the same study, there was no significant association between BMI and atrophic gastritis (25).…”
Section: Discussionmentioning
confidence: 89%
“…A cross-sectional study of 217 patients demonstrated an inverse association between BMI and biopsy-proven intestinal metaplasia (24 (25). In the same study, there was no significant association between BMI and atrophic gastritis (25). In another large-scale retrospective study of 60,261 Korean adults, obesity was significantly associated with endoscopically diagnosed precancerous lesions including atrophic gastritis and intestinal metaplasia, with a multivariable adjusted OR (95% CI) of 1.10 (1.01-1.18; ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But there are many causes of polyps, including chronic intestinal inflammation, aging, abnormal development of immature embryos, low intake of fiber foods, genetic factors, and so on. 21,22 Endoscopic examination revealed gastritis, intestinal metaplasia, and multiple colorectal polyps. However, whether they associated with radionuclide contamination in vivo needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that insulin may potentiate the mitogenic effect of EGF, which in turn activates pathways such as the Ras/mitogen-activated kinase, and promotes also the proliferation of the gastric mucosa cells ( 10 ). Other studies have reported strong association between obesity, SD2 and the development of IM, as well as of gastric cancer ( 11 13 ).…”
Section: Introductionmentioning
confidence: 86%